Patients' views on follow up of colorectal cancer: implications for risk communication and decision making. Issue 933 (1st July 2003) - Papagrigoriadis, S; Heyman, B
Abstract : Background: Medical views about the clinical value and potential detrimental effect on quality of life of postoperative follow up are divided. There is no literature on the views of British patients with colorectal cancer towards the follow up process. Aim: To investigate patients' views and experiences of follow up of colorectal cancer, and to assess their attitudes towards suggested changes to follow up policy. Patients and methods: A total of 156 asymptomatic and disease-free patients with colorectal cancer were identified from the follow up clinic. Recurrence-free status was confirmed through retrieval of computerised clinic letters. A postal survey using a 39 item piloted questionnaire was undertaken. Data analysis generated descriptive statistics and logistic regression models. Results: A response rate of 61% (95) was obtained. Among these respondents, 63% (60) had undergone initial surgery within three years of the time of the survey, and 86% (82) patients expected a further follow up appointment. Majorities of the sample, ranging from 71% (67) to 96% (91), expressed satisfaction with respect to clinic delays, staff conduct and knowledge about their case, consultation time, and being able to discuss personal problems freely. However some patients reported difficulty in discussing sexual problems at the clinic. Appointment imminence caused anxiety, sleep problems, and decreased appetite in 35% (35), 27% (26), and 8 % (8) of patients respectively. However, 78% (74) patients felt reassured and optimistic for the future after receiving results. Such optimism is not necessarily justified in terms of estimated mortality risks. A majority (78%, 66) stated that they would value finding out about the presence of recurrence even if there would be no survival benefit. Nearly half of the sample (48%, 43) felt that they would disagree with the cessation of follow up in any circumstances. Only 47% (42) and 27% (24) indicated that they would accept follow up by a specialist nurse or their general practitioner, respectively. Attitude to follow up was unrelated to reported anxiety before appointments. Only 22% (19) of the sample could identify risk indicators for recurrence, but 64% (61) agreed that they would like to be told what to look for. Discussion: A sample of patients with colorectal cancer expressed a high degree of satisfaction with hospital follow up. Although a substantial minority reported suffering from pre-visit anxiety, most felt that this disadvantage was compensated for by reassuring results, and believed that investigations did not have a significant negative impact on their quality of life. Respondents valued hospital follow up, and half would reject complete discharge or alternative forms of follow up. These findings demonstrate that patients have a different perception of the risk of recurrence than clinicians who would consider the survival prospects for most patients to be more or less unaffected by follow up interventions. Attempted modifications to follow up policies should be introduced with caution, and should take account of patient understanding of medical reasoning. The findings also raise questions about risk communication with patients.